Chemical and biological potentialities of the ethyl acetate extracts of Drynaria quercifolia tuber and leaf (Dhaka University Journal of Biological Sciences, 2015)
The ethyl acetate extracts of Drynaria quercifolia tubers and leaves were studied for their chemical and biological potentialities. The tuber extract was enriched with more reducing power compared to the leaf extract. But, the phenolic content was higher in the leaf extract compared to the tuber extracts. However, both the extracts were comparably cytotoxic and showed broadspectrum antimicrobial activity. The antimicrobial compound in the tuber extract was nonpolar. The findings suggested that the ethyl acetate extracts of D. quercifolia may have active principles for the development of promising phytotherapeutics.Dhaka Univ. J. Biol. Sci. 24(2): 147-152, 2015 (July)